Determinants of Non-Performing Loans of Public Commercial Banks - Srijana Khadka; Ajaya Kumar Khadka (Pravaha, 2022)
The study aimed to examine the effect of profitability on non-performing loans of the Nepalese Commercial Banks. To meet the study’s objectives, three public commercial banks' non-performing loans (NPL) were analyzed using a research methodology that included descriptive and causal comparison methods. The study used a purposive sampling design to select three public commercial banks from 21 populations and used secondary data for the fiscal years 2012/13 to 2021/22. As an alternative data collection technique, the study has 30 observations from the population. This research indicates that remittance and return on equity are significantly associated with non-performing loans. Likewise, remittances negatively influence the NPL of public banks in Nepal, whereas ROE has a favorable effect. NPL was unaffected by GDP, inflation, or ROA to any substantial degree. Researching foreign direct investment and the balance of payments is recommended. Financial institutions should refrain from distributing further credit if they operate under a higher NPL.